OPTIMIZATION OF ALKALINE Α-AMYLASE PRODUCTION BY THERMOPHILIC BACILLUS SUBTILIS - Al-Johani, Nuha Bakeet; Al-seeni, Madeha N.; Ahmed, Youssri Mohamed (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Starch‐degrading amylase enzyme is important in biotechnological applications as food, fermentation, textile, paper and pharmaceutical purposes. The aim of current study to isolate alkaline thermostable α-amylase bacteria and then study the composition of medium and culture conditions to optimize cells growth and a-amylase production. Materials and Methods: Thermophilic amylase producing bacterium was isolated from local hot water-springs in Gazan city Saudi Arabia. Results: Phylogenetic analysis of 16 S rRNA sequence for the strain revealed that the strain have the same sequence of Bacillus subtilis. Maximum amylase production was observed, when B. subtilis cultured in medium containing starch at concentration 0.5%, and 10 g/L peptones as nitrogen source at pH 8.5 in when it was incubated for 48 h at 45°C. Conclusion: An amylase-producing bacterium were isolated from hot-spring water and was identified as B. subtilis. Amylase produced from B.subtilis had optimum temperature 45°C and pH 8.5 in shaking media.